Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1101/359737
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Human salivary amylase gene copy number impacts oral and gut microbiomes

Abstract: SummaryHost genetic variation influences the composition of the human microbiome. While studies have focused on associations between the microbiome and single nucleotide polymorphisms in genes, their copy number (CN) can also vary. Here, in a study of human subjects including a 2-week standard diet, we relate oral and gut microbiome to CN at the AMY1 locus, which encodes the gene for salivary amylase, active in starch degradation. We show that although diet standardization drove gut microbiome convergence, AMY… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 68 publications
1
24
1
Order By: Relevance
“…We observed significant preservative effects on the alpha diversity on only oral and otic samples in vervet monkeys. This is not surprising because microbial communities from each body site are characterized by one or a few signature microbial taxa and preservatives have been shown to affect the presence/absence and abundance of microbial species in the samples (Amato et al, ; Hale et al, ; Poole et al, ; Ochman et al, ; Ott et al, ; Song et al, ; Turnbaugh et al, ; Vlčková et al, ; Yildirim et al, ). The alpha diversity results suggest that relative abundance drives the effect of preservatives rather than simple presence or absence in the oral samples while the phylogeny is needed to see the preservative effect in the otic samples.…”
Section: Discussionmentioning
confidence: 99%
“…We observed significant preservative effects on the alpha diversity on only oral and otic samples in vervet monkeys. This is not surprising because microbial communities from each body site are characterized by one or a few signature microbial taxa and preservatives have been shown to affect the presence/absence and abundance of microbial species in the samples (Amato et al, ; Hale et al, ; Poole et al, ; Ochman et al, ; Ott et al, ; Song et al, ; Turnbaugh et al, ; Vlčková et al, ; Yildirim et al, ). The alpha diversity results suggest that relative abundance drives the effect of preservatives rather than simple presence or absence in the oral samples while the phylogeny is needed to see the preservative effect in the otic samples.…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by studies that have shown that the gut microbiome is heritable, and that the abundance of many microbial taxa is influenced by host genetics [9]. For example, in a recently published study, variation in the copy number of the human salivary amylase gene influenced the gut and oral microbiota [9]. Having differential copy numbers of the human salivary amylase gene influences the expression of the amylase enzyme, and therefore the capacity to degrade starch, which in turn impacts the availability of complex carbohydrates in the gut.…”
mentioning
confidence: 79%
“…Indeed the composition of the gut microbiome is affected by multiple factors including the host genetics. This is supported by studies that have shown that the gut microbiome is heritable, and that the abundance of many microbial taxa is influenced by host genetics [9]. For example, in a recently published study, variation in the copy number of the human salivary amylase gene influenced the gut and oral microbiota [9].…”
mentioning
confidence: 90%
“…Saliva also possesses physicochemical properties keeping the oral cavity moist and well lubricated, which are equally provided by saliva proteins, especially mucins (Frenkel and Ribbeck, 2015;Tabak et al, 1982) . Thus, genetic and dosage variation in the saliva proteome will have important biomedical consequences (Helmerhorst and Oppenheim, 2007;Pajic et al, 2019;Poole et al, 2019;Xu et al, 2017) . At the extreme, malfunctioning of the salivary glands due to, for instance, radiation treatment of head and neck cancer, or caused by the relatively common autoimmune disease, Sjögren's syndrome, can lead to major disruptions in protein homeostasis within saliva causing severe complications in oral health that debilitate patient quality of life (Mavragani and Moutsopoulos, 2019;Vissink et al, 2015) .…”
Section: Introductionmentioning
confidence: 99%